Pengaruh Gaya, Minat, Motivasi, dan Fasilitas Belajar terhadap Hasil Belajar Mata Pelajaran Akuntansi Dasar SMK Negeri 1 Magetan - Fahmi Irfansyah; Agung Listiadi (Edunusa: Journal of Economics and Business Education, 2021)
Education is an effort that is carried out in a planned, orderly manner and plans to create an efficient educational process so that students can improve their abilities. This study aims to determine simultaneously or partially the effect of learning styles, interest in learning, learning motivation, and learning facilities on learning outcomes in basic accounting subjects at SMK Negeri 1 Magetan. This study uses a quantitative research model. The population in this study consisted of 114 students where the researchers took 106 students to become a sample which was calculated using probability sampling techniques using simple random sampling. This research data collection technique using a questionnaire distributed online and analyzed using multiple linear regression. The results showed that 1) partially learning styles, interest in learning, learning motivation, and learning facilities had a significant and positive effect on student learning outcomes, and 2) simultaneously learning styles, interest in learning, learning motivation, and learning facilities had a significant effect and has a positive value on the student learning outcomes.